Risk factors for hyperemesis gravidarum in the Peruvian maternal-perinatal institute - Ángeles-Olaza, Gianina Jesús (2024)
Introduction: Hyperemesis gravidarum (HG) is a disorder of pregnancy characterizedby severe nausea and vomiting that can lead to serious complications. It affectsapproximately 0.5%-2% of pregnant women globally, being more common in multiplepregnancies and in young women. Objective: To identify the risk factors associatedwith hyperemesis gravidarum in women attended at the Instituto Nacional Materno Perinatal in Lima, Peru, during the year 2022. Materials and Methods: A case-control study including 126 pregnant women (63 cases with HG and 63 controls) was performed. Data collected on factors associated with hyperemesis gravidarumsuch as extreme maternal age, higher education level, maternal obesity, maternalhCG concentrations in the first trimester, parity, multiple pregnancy, female fetus,history of mental illness, hyperthyroidism and hydatidiform mole were analyzed.Logistic regression was used to avoid confounding variables. Results: Multivariateanalysis adjusted for possible confounding variables indicated that higher educationlevel was a protective factor for hyperemesis gravidarum but was not statisticallysignificant. In contrast, maternal obesity, high hCG concentrations during the firsttrimester, nulliparity, and having a female fetus were factors that increased the riskof hyperemesis gravidarum and were statistically significant. Conclusion: The studyfound that maternal obesity, high hCG concentrations, nulliparity, and gestation of afemale fetus were significant risk factors for hyperemesis gravidarum, while a highereducation level could be a protective factor, though not a significant one.